Developing support service for victims of hate crime - Dunn Peter (Temida, 2004)
This article describes the nature and development of Victim Support’s services to victims of hate crime in England and Wales. It provides definitions of hate crime, information about its extent, and considers why services for victims of some forms of hate crime have developed faster than others. It concludes with a summary of points made during a discussion at the 2004 European Forum for Victim Services conference about whether or not services to victims of hate crime should be provided by mainstream victim services or specialist agencies.